Reaksi Pasar Modal Dalam Menilai Stock Split Perusahaan Di Bursa Efek Indonesia - irawan irawan; Ari Irawan (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The purpose of this study is to prove the absence of market reaction as a result of stock splits. The population used for this study is a company that conducts a stock split policy registered with the IDX in the period 2019-2020 as many as 15 companies. Data analysis techniques using comparative study with pired sample t-test analysis. The results of the study proved that there was no significant difference in closing prices before and after the publication of stock split. The results of subsequent research proved there was a significant difference in Trading Volume Activity before and after the stock split. The implications of the results of this study show that companies that do stock splits can cause market reactions to increasing trading volume activity in the capital market as a signal that the stock split event is a policy that is awaited by the market so that the reaction is quite large for investors. This result is in accordance with the trading range theory which states that stock split events will cause increased trading volume or increased liquidity due to prices that are more attractive to investors.